1986
DOI: 10.1007/bf00333978
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by pH of the growth medium in Aspergillus nidulans

Abstract: In the fungus Aspergillus nidulans the levels of a number of enzymes whose location is at least in part extracellular (e.g. acid phosphatase, alkaline phosphatase, phosphodiesterase) and of certain permeases (e.g. that for gamma-amino-n-butyrate) are controlled by the pH of the growth medium. For example, at acidic pH, levels of acid phosphatase are high and those of alkaline phosphatase are low whereas at alkaline pH the reverse is true. Mutations in five genes, palA, B, C, E and F, mimic the effects of growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
234
1
14

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(263 citation statements)
references
References 24 publications
5
234
1
14
Order By: Relevance
“…The regulation of this adaptive response has proved to be highly complex, not only because of the identification of a large number of genes involved in the signaling of Pi starvation, but also because the synthesis and secretion of these enzymes are under the action of nitrogen, carbon and pH regulatory circuits (8,13,19). The pH regulatory mechanism ensures that extracellular enzymes are secreted only at pH values at which they can function effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of this adaptive response has proved to be highly complex, not only because of the identification of a large number of genes involved in the signaling of Pi starvation, but also because the synthesis and secretion of these enzymes are under the action of nitrogen, carbon and pH regulatory circuits (8,13,19). The pH regulatory mechanism ensures that extracellular enzymes are secreted only at pH values at which they can function effectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of nucleic acids as sources of inorganic phosphate (Pi) is based on the induction of structural proteins, permeases, and enzymes of the cell wall, in addition to the secretion of a variety of proteins and hydrolytic enzymes such as nucleases and acid and alkaline phosphatases in response to both Pi starvation and environmental pH signaling. This metabolic machinery permits the fungi, and other microorganisms, to use these macromolecules as sources of essential nutrients within a broad ambient pH range (8,11,17,19). Thus, it is also important to understand the metabolic responses that govern homeostatic pH and extracellular pH sensing in dermatophytes, since the pathogenicity of many microorganisms has been demonstrated to depend on the sensing of ambient pH in the host and on the ability to adapt, which involves installation, development, and survival in the host.…”
Section: Introductionmentioning
confidence: 99%
“…pH regulation of gene expression is mediated by the zinc finger transcription factor PacC, whose 73-kDa full-length translation product is proteolyzed to yield a 29-kDa N-terminal fragment able to activate transcription of genes expressed at alkaline pH and prevent transcription of genes expressed at acid pH (15,17,19). The products of six genes, palA, -B, -C, -F, -H, and -I, form a signal transduction pathway through which alkaline ambient pH is able to elicit the conversion of the full-length form of PacC to the functional proteolyzed form (1,3,5,15,19). Loss-of-function mutations in these pal genes prevent this proteolytic conversion and mimic the effects of growth at acidic pH (1,3,5,7,15,18).…”
mentioning
confidence: 99%
“…The products of six genes, palA, -B, -C, -F, -H, and -I, form a signal transduction pathway through which alkaline ambient pH is able to elicit the conversion of the full-length form of PacC to the functional proteolyzed form (1,3,5,15,19). Loss-of-function mutations in these pal genes prevent this proteolytic conversion and mimic the effects of growth at acidic pH (1,3,5,7,15,18).The mechanism of ambient pH signal transduction is an intriguing subject of scientific and biotechnological importance. We have previously shown that the palB gene product is likely to be a cysteine protease of the calpain family, albeit not the protease responsible for the final conversion of PacC to its functional form (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation